Resistance and motivation factors in using mobile financial service for public / Siti Zuraikah Ab Karim - Ab Karim, Siti Zuraikah (2014)
Mobile phone is a device that use to connect people through calling and messaging but with today's advance technology, mobile phone has equipped with the Internet connection that can give advantage in the creation of mobile financial services. Basically, mobile financial banking is a device which can be used in making financial transaction through a mobile phone especially smartphone. This study is to identify resistance and motivational factors that influence the intention in using mobile financial services. Using questionnaire that was construct by adapting from previous study, a survey was conduct with 156 respondents randomly in the area of Kota Kinabalu, Sabah. Result from the study shows that image barrier are the significant factor which make people resist to use mobile financial services whereas relative advantage, trialability, facilitating condition, and perceive enjoyment are the significant factors that motivates people in using mobile financial services. The findings in this study will give adequate information to marketers, mobile manufacturers, financial institutions, as well as researcher in enhancing the used of mobile financial services in today lifestyle.